MECHANISMS OF FORMATION OF KIDNEY FIBROSIS BASED ON MICROVASCULAR LESIONS - E. S. Levitskaya (Медицинский вестник Юга России, 2017)
The review deals with the description of the mechanisms involved in the formation of kidney fibrosis. Presented molecular factors activation of the pathological process, signaling pathways, competent cells with synthetic provospolitelnyh mediators, the role of epithelial-mesenchymal transition in the development and progression of renal fibrosis. Demonstrated evidence of the importance of the remodeling of the renal arteries of small diameter in the development and progression of renal fibrosis tissue. Sources of information on topics Review article full disclosure, a presentation of the current views on the study of this problem, use the database PubMed citations, RISC, Scopus, Web- Mathematical Sciences, Google Scholar, Copernicus index, Ulrich Periodicals Directory.